DESIGN AND DEVELOPMENT OF THE ICT NETWORK INFRASTRUCTURE PROJECT OF CTU – ARGAO CAMPUS - Benolirao, Eingibert C. (Journal of Agriculture and Technology Management, 2012)
The main objective of the study was to design and develop an Improved ICT Network Infrastructure in the University. The establishment of this Improved ICT Network Infrastructure will help enhance the competence of the Cebu Technological University (CTU) – Argao Campus in the performance of its mandate as an institution of higher learning. The design was created through a state of the art network infrastructure with 802.1x wired and wireless networks, and built a new data center for our Management Information System (MIS), Web Server for the campus website and an LCMS online course for instructional use. The components of the design and development of such infrastructure involves a Network Improvement Program: (Wired Cablings, Wireless LAN, & Edge Infrastructure Project) which prioritizes the identification and replacement of old cablings, with departmental network equipment and resilient campus routes to follow. Then a wireless LAN will be established for users having wireless gadgets like laptops, notebooks, and the like. Another component of the project was the Topology and Physical Layout Design which uses networking technology tools and simulation software to assist in the design topology, layout and configurations to optimize the network performance. The new network brings greater uptime, reliability and functionality to the students. Each department of the campus uses the network in different ways and these uses are starting to take on a lot of sophistication in terms of technologies such as multicast traffic, video streaming, wireless devices such as wireless laptops, pervasive devices such as PDAs, PC tablets, collaborative teaching, etc. Thus, the new CTU – Argao Campus Network will not only increase reliability, but benefit the research and educational goals of the university. There will be increased productivity in terms of education and development of multimedia instructional materials with the aid of ICT facilities and equipment in the improved ICT Network Infrastructure. A better and appropriately managed R&D activities leading to a coordinated R&D program, and an effective technology transfer through the provision of improved ICT Network Infrastructure and facilities.